Role of Amorphous Phases in Enhancing Performances of Electrode Materials for Alkali Ion Batteries - Xiong, Fangyu; Tao, Haizheng; Yue, Yuanzheng (Frontiers in Materials, 2020)
As one of the most competitive energy storage systems owing to their high energy density, conversion efficiency, long lifetime and environment friendliness, alkali ion batteries have been widely used and continue to exhibit their potential to be the crucial components of future energy technologies. To further improve electrochemical performances of alkali ion batteries, great efforts have been put into the development of advanced electrode materials. However, scientists are facing great challenges in developing superior electrode materials due to the limitation of the existing technologies. Therefore, we recently chose a different route, that is, the amorphization engineering, to develop high performance electrodes. Here, we review some recent studies about the role of amorphous phases in promoting electrochemical performances of both cathodes and anodes for alkali ion batteries. In addition, we review some progress in revealing the microscopic mechanisms of the increased ionic/electronic transport as well as the enhanced structural stability in electrodes, achieved by amorphization engineering.